2021
DOI: 10.3389/fnhum.2021.635304
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Distress and Offspring Neurodevelopment: Challenges and Opportunities for Pre-clinical Research Models

Abstract: Pre-natal exposure to acute maternal trauma or chronic maternal distress can confer increased risk for psychiatric disorders in later life. Acute maternal trauma is the result of unforeseen environmental or personal catastrophes, while chronic maternal distress is associated with anxiety or depression. Animal studies investigating the effects of pre-natal stress have largely used brief stress exposures during pregnancy to identify critical periods of fetal vulnerability, a paradigm which holds face validity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 252 publications
0
9
0
Order By: Relevance
“…The negative effect of persistently high levels of glucocorticoid during pregnancy was found both in animal models, where it induces anxiety-like behaviors [ 40 , 41 ], and in in vitro models, where it is associated with a reduction in proliferation of neural progenitor cells [ 42 ] or a specific expression of genes associated with high vulnerability to psychiatric disorders [ 43 ]. The implications of other biological pathways, such as changes in placenta function and inflammatory or epigenetic mechanisms, have been widely discussed elsewhere (for a review, see Fitzgerald, Parent, Kee and Meaney [ 44 ]). In addition, neuroimaging studies conducted in infants of women with antenatal mental health problems showed differences in brain structure and connectivity of regions specifically involved in threat assessment and cognitive appraisal [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The negative effect of persistently high levels of glucocorticoid during pregnancy was found both in animal models, where it induces anxiety-like behaviors [ 40 , 41 ], and in in vitro models, where it is associated with a reduction in proliferation of neural progenitor cells [ 42 ] or a specific expression of genes associated with high vulnerability to psychiatric disorders [ 43 ]. The implications of other biological pathways, such as changes in placenta function and inflammatory or epigenetic mechanisms, have been widely discussed elsewhere (for a review, see Fitzgerald, Parent, Kee and Meaney [ 44 ]). In addition, neuroimaging studies conducted in infants of women with antenatal mental health problems showed differences in brain structure and connectivity of regions specifically involved in threat assessment and cognitive appraisal [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed existing literature in this area of research, and shared our experience and thoughts on study design and potential technical challenges, with the hope that more research will be invested in this area to allow a better understanding of fetal reprogramming in response to placental insufficiency and other intrauterine environment. Indeed, not only is long-term health and disease of the offspring affected by placental insufficiency and FGR, studies have also found maternal distress, prepregnancy health, and other pregnancy complications to affect offspring well-being [58]. We believe that in the study of the dynamics of transcriptional regulation in fetal reprogramming, combining cffRNA and high-throughput sequencing serves as the best approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, persistent anxiety is more concerning and associated with adverse effects for maternal mental health and birth outcome 3 , such as increased risk of preterm birth, low birth weight, birth intervention, and postnatal depression 2,[4][5][6][7][8][9] . The consequences of maternal anxiety extend far beyond pregnancy and birth, with adverse psychosocial outcomes in the offspring and increased risk of emotional and behavioral problems in children [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%